Can agricultural protectionist policies help achieve food security in Nigeria? - Gao, Ya; Zhao, Tianhui; Xu, Xiuli; Ndidiamaka, Agbo Patience (Frontiers in Sustainable Food Systems, 2023)
This study mapped the dynamic interaction of narratives regarding Nigeria's pursuit of rice self-sufficiency and related trade policies since the 1970s to explore whether agricultural protectionist policies can help achieve food security in Nigeria. Developing agricultural trade policies that simultaneously secure imported food supplies and protect domestic agricultural development is a challenging task. Nigeria's protectionist policies have a controversial agenda. Few studies have investigated the dynamic process of rice production and trade policy from a historical viewpoint; our study fills this gap. Through mapping Nigeria's pursuit of rice self-sufficiency over the past 50 years, we found that seesawed trade policy parallels complex rice development, leaving imported rice dependence unchanged. Regardless of when policies switch to trade protection or liberalization, the procedure does not directly lead to increased rice production. Since much exploration is needed regarding how to achieve food security in Nigeria, we also identify three new dimensions for future food security research based on our findings' optimal recommendations.